Effect of coating by perfluorosulfonated ionomer film on electrochemical behaviors of Pt(111) electrode in acidic solutions - Sonsudin, F.; Masuda, T.; Ikeda, K.; Naohara, H.; Uosaki, K. (Chemical Soc Japan, 2010)
Electrochemical behaviors of bare and perfluorosulfonated ionomer (PFSI) film-coated Pt(111) electrodes in perchloric and sulfuric acid solutions were investigated. While current peaks corresponding to specific adsorption and desorption of anions were clearly observed at the bare electrode, no such peaks were observed at the PFSI-coated electrode, showing that anions do not reach the electrode surface because of the cation-selective nature and/or adsorption of PFSI film. Although no structural change was observed by repetitive potential cycling as far as positive potential limit was more negative than that of oxide formation, significant structural change was noticed during potential cycling if the anodic potential limit was made more positive than oxide formation potential.